“Neither honey nor gourd”: The color fortunes of a brown visual arts teacher (Revista Apotheke, 2021)
This text is configured as a narrative look at the construction of professional identity from a middle-brown Visual Arts teacher. Emphasizes interpretations of the term “color fortune”, using inflection points of memory, seeking to provide, through autobiographical reflections, understandings about how formation and praxis in the classroom connect concepts and practices in the experience of being/become a teacher. Thus, in a cartographic perspective, each point translates a passage that combines geographical and cultural territories with the production of belonging, reviewing the ways of seeing, from the voice to the body felt in analysis about the current moment of the pandemic of covid19. For these reasons, the paths taken attempt to dialogue with others in a painting that portrays the present and open more broader and contextualizing spaces, in which skin tones are a point of sharing and not of invisibilities in and for the formation in Visual Arts Teachers Education.
Keywords: identity; visual arts teachers education; visual arts